Phytoestrogens in NAFLD: Potential Mechanisms of Action - Li, Hui; Jia, Erna; Jiao, Jian (Hormone and Metabolic Research, 2020)
Many studies have shown that estrogen has a protective effect on premenopausal women with metabolic disorders and non-alcoholic fatty liver disease. Estrogen supplements may, at least in theory, prevent the development and progression of NAFLD, while the possibility of inducing cancer limits its application in practice. Phytoestrogen is extracted from plants, whose molecular structure and biological activity are similar to those of mammals' estrogen, therefore, could replace the role of estrogen and prevent the occurrence of adverse reactions to estrogen. This article reviews the published literature related to phytoestrogens and NAFLD as well as suggest the possible mechanisms that may underlie the association between phytoestrogens and NAFLD. It is hoped to provide basis for the treatment of NAFLD with phytoestrogen.
Keywords: phytoestrogens; NAFLD; antioxidant; signaling pathway